PENERAPAN INTEGRATED MARKETING COMMUNICATION (IMC) OLEH AIOLA EATERY DALAM KEBERHASILAN PROMO HALAL BI HALAL - Annisa Indira Putri; Dwi Ananda Rizka Octavia; Mohammad Insan Romadhan (RELASI, 2022)
Intense competition in the era of the industrial revolution and the development of digital technology is a challenge for a company to have an effective and targeted marketing strategy. Integrated Marketing Communication (IMC) is a marketing strategy that must be owned by a company, including a Food n Beverage company. Aiola eatery is one of the most successful FnB companies in Surabaya. This success is accompanied by a variety of good marketing strategies. This study aims to find out how the IMC implementation carried out by Aiola Eatery in the Halal bi Halal promo and at the same time analyzes its success. This research uses qualitative method with constructivism paradigm as the basis. The study was conducted by two researchers with data collection techniques using in-depth interviews with Marketing Communication from Aiola Eatery as primary data and secondary data in the form of promo designs and promo recap results. The results of this study are Aiola Eatery uses 4 kinds of IMC strategies, namely public relations & publicity, digital marketing, sales promotion and direct marketing. This strategy supports the success of Aiola Eatery in making promos, one of which is the Halal bi Halal promo with targeted results. In addition, Aiola Eatery also uses IMC as an effort to align customers both online or on social media and those who come in person or dine in.